Vladimir Propp’s Taxonomic Model of Narrative Functions in Selected Jane Austen’s Novels (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This research aims to identify the taxonomic model of narrative functions by Vladimir Propp and to find out how these functions are distributed among the dramatis personae (spheres of action) in selected Jane Austen’s novels, they are Pride and Prejudice, Emma, Sense and Sensibility, and Persuasion. This descriptive qualitative research aims to describe the phenomenon and its characteristics. The data were collected qualitatively by documenting, examining, and classifying thoroughly. The results indicate 20 functions in Pride and Prejudice, 14 functions in Emma, 15 functions in Sense and Sensibility, and 22 functions in Persuasion. From the results, this research shows that Jane Austen’s fairytale novels are compatible and match the taxonomic model of narrative functions by Vladimir Propp. The results also show four dramatis personae in each novel (Hero, Villain, Donor, Helper). As for Sense and Sensibility, it has a False Hero. Furthermore, the results share similarities in the 13 functions and the happy endings marriage (W). At the same time, the differences are located in the different number of functions and their distribution, which influence the overall narratives.